Performance Behaviour of Fully Grouted Rock Bolt as Support System - Singh, Deepanshu R.; Mishra, Arvind K. (Journal of Mines, Metals and Fuels, 2017)
Rock bolts are one of the most prominent and economical techniques of rock stabilization used widely in various applications such as mining, tunneling, surface slope stabilization. Various researchers have found that efficacy of rock bolt system depends on the many factors such as annulus space, type of bolt, grouting media, installation mechanism and positioning. Since its inception, many researchers have studied the behaviour of bolts experimentally and analytically. At present in Indian mining industry, the use of fully grouted rock bolts are increasing rapidly owing to the number of accidents in underground mainly due to roof fall. This paper reviews the performance of fully grouted rock bolts under axial loading conditions and presents a case study of an Indian underground metal mine. The review provides an overview of the need for rock bolts to support the roof rock and the bolting system used in Indian mines along with characteristic parameters such as ultimate load, displacement and failure mode under axial load. A study was undertaken to understand the behaviour of fully grouted un-tensioned rebar bolts in an Indian metal mine having competent host rock. The case study describes the performance of fully grouted un-tensioned rock bolt supporting the hangingwall at a depth of 150 m from the surface. The anchorage strength of the bolts were determined in field conditions by conducting pull out test at different durations from the time of installation of the bolt. The generated load-displacement curve shows the de-bonding nature of the installed bolts under axial loading conditions. The safety factor was calculated for the designing of support system of the mine and the rock load was found using empirical equations using rock mass rating. The safety factor calculation resemble successful application of un-tensioned roof bolt system in supporting an underground metal mine.